Silica–Gold Core–Shell Nanosphere for Ultrafast Dynamic Nanothermometer. (20th December 2013) - Sun, Hongtao; Sun, Xiang; Yu, Mingpeng; Mishra, Ashish Kumar; Huang, Liping; Lian, Jie
<x xml:space="preserve">Abstract</x> Effective temperature measurements are of significance for a fundamental understanding of nanosystems and functional applications, requiring ultimate miniaturization of thermometers with reduced size but maintained sensitivity, simplicity, and accuracy of temperature reading. Grand challenges exist for scenarios of thermal shock or combustion where materials may be subjected to extreme thermal flux and drastic temperature variations, and dynamic thermal sensors with an ultrafast response are yet to be developed. Here, an innovative design of silica–gold core–shell (SiO2@Au) nanospheres is demonstrated as a potential dynamic sensor with a sub‐second response time and accurate temperature determination based on the strong temperature dependence of the thermally induced morphological self‐reorganization and characteristic surface plasmon (SP) absorption of the metal shell. The irreversible thermally induced morphological and optical signatures behave as characteristic "fingerprints" for temperature recordings, allowing the retrieval of thermal history ex‐situ. As compared with current nanothermometer technologies such as metal‐filled nanotubes, the core–shell nanosphere‐based dynamic thermosensor offers synergistic advantages of ultrafast time response, fast readout, permanent recording of thermal history, and ex‐situ capabilities for effective temperature measurements.